Analysis of Elementary Students' Participation Levels in Hockey Extracurricular Activities - Rahma Dwi Aulia; Yogi Akin; Wulandari Putri (Universitas Negeri Semarang, 2026)
This study aims to determine the level of participation of elementary school students in hockey extracurricular activities in Bandung City. The study used a quantitative approach with a descriptive method to describe the level of student participation objectively based on numerical data. The research sample consisted of 50 students who participated in hockey extracurricular activities. The instrument used was a closed questionnaire with 18 statements using the Guttman scale, where the answer